Composite film of magnesium alloy chemical conversion microarc oxidation. (December 2014) - Shao, Z.; Kong, B.; Zhao, Y.; Cai, Z.
<x content-type="archive" xml:space="preserve">Abstract</x> The dark composite ceramic film was prepared on AZ91D magnesium alloy with a new method which combined chemical conversion with microarc oxidation. Using L16 (45) orthogonal test to optimise the optimum technological conditions of the chemical conversion treatment fluid. The surface morphologies, chemical composition and structure of the film were examined by SEM and XRD. The corrosion resistance performances of the films were investigated by electrochemical measurements (in 3·5 wt-%NaCl aqueous solution). The results showed Zn element was introduced into the microarc oxide ceramic films by chemical conversion pretreatment. The main composition of composite ceramic film was ZnO, ZnO2 and Mg3 (PO4)2 and the surface of the composite ceramic film was smooth, compact and even dark. The saline soaks experiment (72 h) and electrochemical analysis showed corrosion resistance of ceramic film was improved obviously. Adding glycerin can make microarc oxidation reaction more stable and ceramic film of the discharge apertures was smaller. This further increased the density of the film layer and improved the corrosion resistance of the film.